2020
DOI: 10.1080/13880209.2020.1818790
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC-MS/MS method for pharmacokinetic and bioavailability determination of five bioactive components in raw and various processed products of Polygala tenuifolia in rat plasma

Abstract: (2020) UHPLC-MS/MS method for pharmacokinetic and bioavailability determination of five bioactive components in raw and various processed products of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…55 However, the absorption of DISS could be promoted by multiple conditions, such as other ingredients in Polygalae Radix, compatibility with other herbs, 56 disease state 57 and processing procedure. 53 In addition, brain distribution research of DISS is limited. A report mentioned that DISS could distribute into brain (~7 ng/g) when rats…”
Section: 6'-disinapoyl Sucrose Decreased Paralysis Of Aβ 1-42 Transge...mentioning
confidence: 99%
See 2 more Smart Citations
“…55 However, the absorption of DISS could be promoted by multiple conditions, such as other ingredients in Polygalae Radix, compatibility with other herbs, 56 disease state 57 and processing procedure. 53 In addition, brain distribution research of DISS is limited. A report mentioned that DISS could distribute into brain (~7 ng/g) when rats…”
Section: 6'-disinapoyl Sucrose Decreased Paralysis Of Aβ 1-42 Transge...mentioning
confidence: 99%
“…Although the pharmacokinetics of DISS in C . elegans is not obvious, many studies reported that DISS was absorbed into blood very quick when rats were orally administered DISS, Polygalae Radix or compound containing Polygalae Radix 53,54 . However, the bioavailability of DISS in rats was not very high and it was eliminated from blood, and brain is also very quick because oligosaccharide esters could be hydrolysed to secondary glycosides or aglycones 55 .…”
Section: Disussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazilian Journal of Development, Curitiba, v.7, n.11, p. 104656-104670 nov. 2021 Zhao et al (2020) estabeleceram um método UHPLC-MS/MS para detectar simultânea e quantitativamente a sibiricose A5, sibiricose A6, 3,6′-disinapoil sacarose, tenuifolisideo A e TMCA (compostos presentes nas raízes de Polygala tenuifolia Wild) em plasma de rato. Este estudo não só determinou os níveis de TMCA nas raízes da planta crua, mas também em raízes fervidas com alcaçuz e também do cozimento de mel, pois este tipo de processamento é comumente utilizado na prática clínica chinesa.…”
Section: Fonte: Autoresunclassified
“…11 Processing technology can promote the bioavailability of TMCA and provide scientific basis for future clinical application and processing mechanism. 12 In the pharmaceutical industry, especially in the purification, crystallization, and other processes, accurate solubility data for improving the recovery rate and product quality is of great significance. However, the solubility of TMCA was much lower in some solvents, which limited its industrial application.…”
mentioning
confidence: 99%